Health-related quality of life in school children: validation of instrument, child self assessment, parent-proxy assessment and school nursing documentation of health check-ups - Laaksonen, Camilla (Annales Universitatis Turkuensis D 1003, 2012)
The aims of this study were to validate an international Health-Related Quality of Life (HRQL) instrument, to describe child self and parent-proxy assessed HRQL at child age 10 to 12 and to compare child self assessments with parent-proxy assessments and school nursing documentation. The study is part of the Schools on the Move –research project. In phase one, a cross-cultural translation and validation process was performed to develop a Finnish version of Pediatric Quality of Life Inventory™ 4.0 (PedsQL™ 4.0). The process included a two-way translation, cognitive interviews (children n=7, parents n=5) and a survey (children n=1097, parents n=999). In phase two, baseline and follow-up surveys (children n=986, parents n=710) were conducted to describe and compare the child self and parent-proxy assessed HRQL in school children between the ages 10 and 12. Phase three included two separate data, school nurse documented patient records (children n=270) and a survey (children n=986). The relation between child self assessed HRQL and school nursing documentation was evaluated. Validity and reliability of the Finnish version of PedsQL™ 4.0 was good (Child Self Report α=0.91, Parent-Proxy Report α=0.88). Children reported lower HRQL scores at the emotional (mean 76/80) than the physical (mean 85/89) health domains and significantly lower scores at the age of 10 than 12 (dMean=4, p=<0.001). Agreement between child self and parent-proxy assessment was fragile (r=0,4, p=<0.001) but increased as the child grew from age 10 to 12 years. At health check-ups, school nurses documented frequently children’s physical health, such as growth (97%) and posture (98/99%) but seldom emotional issues, such as mood (2/7%). The PedsQLTM 4.0 is a valid instrument to assess HRQL in Finnish school children although future research is recommended. Children’s emotional wellbeing needs future attention. HRQL scores increase during ages between childhood and adolescence. Concordance between child self and parent-proxy assessed HRQL is low. School nursing documentation, related to child health check-ups, is not in line with child self assessed HRQL and emotional issues need more attention.